No effects of fire, large herbivores and their interaction on regrowth of harvested trees in two West African savannahs. (6th October 2015) - Tredennick, Andrew T.; Karembé, Moussa; Dembélé, Fadiala; Dohn, Justin; Hanan, Niall P.
Abstract: Theory and empirical evidence for the impacts of fire and herbivory in savannahs is well established – they are top‐down disturbances that maintain savannahs in disequilibrium states away from potential tree cover. In African savannahs, the demand for fuelwood is extremely high, so tree harvest likely also has an impact, both directly and indirectly, on tree cover, density and biomass. Many savannah trees resprout vigorously from the base after harvest. However, harvested trees regenerate as saplings susceptible to fire and browsing, so harvest may have important demographic consequences. Here, we report the effects of tree harvest, and its interaction with fire and herbivory, on savannah dynamics by analysing woody regrowth following a harvest in arid Sahelian and mesic Guinean savannahs in Mali, West Africa. Tree harvest resulted in an overall reduction in wood production per tree compared to growth in nonharvested trees. Regrowth, either biomass or height, did not differ among fire and herbivory treatments. Our results suggest that the resprouting abilities that savannah trees have evolved to cope with frequent fire are essential for surviving tree harvest and subsequent disturbance. In these savannahs, regrowth is rapid enough in the first growing season to escape the impact of dry season fires.